Ekstraksi Fitur Menggunakan Haar Wavelet Transformation Pada Klasifikasi Jenis Bakteri Air - Sepyan Purnama Kristanto; Lutfi Hakim; Dianni Yusuf (STMIK Budi Darma, 2022)
Bacteria is one of the species that live in groups and is on some media close to humans. As the media closest to humans, water has become one of the most expensive and mutating places for bacteria. Various kinds of bacteria live in raw water that comes from some sources of water that often cause various diseases for humans. Many good diseases that transmit and do not transmit are often found in water, especially in households. With the various problems that arise, there needs to be a system that can detect and determine the type of bacteria in the water. The researchers built a bacterial classification system in water to facilitate the filter and sterilization process from these problems. This system utilizes the haar wavelet method, which has a good reputation in the transformation process. The accuracy results obtained in this study are very satisfactory, with an accuracy rate of 90% in detecting the type of bacteria.